Molecular basis of peripheral olfactory plasticity in Rhodnius prolixus, a Chagas disease vector - Latorre Estivalis, Jose M.; Omondi, Bonaventure A.; DeSouza, Og; Oliveira, Ivana Helena R.; Ignell, Rickard; Lorenzo, Marcelo G. (Frontiers in Ecology and Evolution, 2015)
Olfaction is fundamental for most animals and critical for different aspects of triatomine biology, including host-seeking, reproduction, avoidance of predators, and aggregation in shelters. Ethological and physiological aspects of these olfactory-mediated behaviors are well understood, but their molecular bases are still largely unknown. Here we investigated changes in molecular mechanisms at the peripheral olfactory level in response to different physiological and developmental conditions. For this, the antennal expression levels of the odorant (Orco) and ionotropic (IR8a, IR25a and IR76b) coreceptor genes were determined in Rhodnius prolixus by means of quantitative real-time PCR (qRT-PCR) analysis. Gene expression changes were analyzed to test the effect of feeding and imaginal molt for both sexes. Moreover, we analyzed whether expression of these genes changed during the early life of adult bugs. Under these conditions bugs display distinct behavioral responses to diverse chemical stimuli. A significantly decreased expression was induced by blood feeding on all coreceptor genes. The expression of all genes was significantly increased following the imaginal molt. These results show that olfactory coreceptor genes have their expression altered as a response to physiological or developmental changes. Our study suggests that olfactory coreceptor genes confer adaptability to the peripheral olfactory function, probably underlying the known plasticity of triatomine olfactory-mediated behavior.